Концептуальні питання теорії права - Коновалова, В. О.; Мишков, Я. Є. (My University, 2016)
Стаття передбачає історичний екскурс виникнення методики розслідування злочинів як одного з розділів криміналістики, який синтезує техніку і тактику науки. Наводиться аналіз криміналістичної літератури і називаються нові дослідження у напрямі розвитку методики розслідування. Акцентується увага на інноваціях в методиці розслідування злочинів. // The article provides a historical excursion to the emergence of a methodology for investigating crimes as one of the sections of criminology, which synthesizes the technique and tactics of science. The analysis of forensic literature and are called new research in the direction of development of the investigation methodology. The focusing on innovations in the method of investigation of crimes.
Keywords: методика розслідування злочинів; інновації в методиці розслідування злочинів; транснаціональні злочини; methodology for investigating crimes; innovation in the method of investigation of crimes; transnational crimes